PERENCANAAN PROGRAM KETERAMPILAN MEMBATIK UNTUK PESERTA PAKET C DI PKBM AZ-ZAHRA KABUPATEN KEPAHIANG - Fela Jasdi Artawati; Agus Zainal; Ilham Abdullah (Jurnal Pendidikan Sepanjang Hayat, 2021)
The purpose of this study was to determine the planning of the package C learning program at PKBM Az-Zahra, Kepahiang Regency. This study refers to several indicators studied, namely the target of activities, the form of planning, the people involved, and the identification of programs carried out by the institution for the package C learning program at PKBM Az-Zahra. This study uses the method of Focus Group Discussion (FGD). The results of this study indicate that before the implementation of the batik skills program at PKBM Az-Zahra, a plan was first carried out. In planning the batik skills program for package C participants at PKBM Az-Zahra, the institution held a meeting with the organizational structure to set activity targets and identify the program. The target of activities in planning the batik skills program at PKBM Az-Zahra is to improve the life skills of students in package C through the batik program, train participants in package C so that their work has a selling value. As well as joining business groups that have been provided by institutions (Umeak Kain Diwo and Rumah Kreatif) and creating new entrepreneurs. The people involved in planning the batik skills program at PKBM Az-Zahra are operators, tutors, managers, coaches, and all teaching staff of PKBM Az-Zahra.